PENGARUH STRATEGI ADAPTASI TERHADAP HUBUNGAN SOSIAL TEMAN SEBAYA PADA KOMUNITAS PENGHUNI KOS DI KECAMATAN TAMPAN - Lisa Anggraini; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in the district of Kecamatan Tampan. The purpose of this research is to know the characteristics of peers relationship of students who are boarding in Kelurahan Simpang Baru district of Kecamatan Tampan, and reviewing the influence of the student adaptation strategy of the community boarding In the village of Simpang Baru charming subdistrict. The topic of focus of this research is the adaptation strategy of students who kost in the village of Simpang Baru Kecamatan Tampan district. The samples in this study amounted to 100 people. The authors use quantitative methods and use accidental sampling techniques. Data instruments are observations, polls and documentation. From the research conducted, the authors found that 84.0% of new students get closer to other cost occupants when they start living in the settlement-Kosan and 64% of old students often chat with other boarding dwellers during leisure time Were. Research has also found that there are several student strategies to adapt at Kos-kosan. That is as follows: Active strategies 72% of respondents are easy to get along with a new cost partner. Passive strategy, 28% of respondents said they do not like to travel too often with peer activities at cost. Network strategy, 72% of respondents said they like to participate in each activity together with a cost partner.  Research finds regression coefficients for employee performance positive value, meaning adaptation strategies positively affect the social relations of peers on the cost-dwelling community of handsome subdistrict. Variable regression coefficient value adaptation of 1.558. The meaning is that every increase of one unit of adaptation strategy will increase social relations by 1.558.